What Microservices Can Learn From Enterprise Information Integration - Schwarz, Georg-Daniel; Riehle, Dirk (HICSS-53, 2020)
Microservices are an architectural style in which each service typically provides the complete stack of functions from a user or application programming interface through a domain model all the way to storage for that model. As a consequence, querying conjunct data from different microservices becomes a non-trivial engineering task. In this article, we review older and established general data integration theory in the enterprise context and then compare current microservice practice with enterprise information integration (EII) theory as an established approach to data integration. We find that microservices do not utilize all possible approaches for data integration that are common in enterprises. Specifically, microservices use middleware only partially and databases are not used at all to integrate data. Therefore, we further investigate whether, when, and how these two approaches can be used in a microservices context and present our findings. With our findings, we (i) clear the way for fellow researchers to investigate and improve unused integration strategies with microservices and (ii) raise the awareness of practitioners that some integration strategies may not work out of the box with microservices as they do in EII.<br
Keywords: microservices; integration; EII